Investigation of the effects of codeposition of tin on the suppression of hydrogen evolution in nickel electrodeposition system - Tan, Ronald Teck Ee (2015)
The aim of the project is to suppress hydrogen evolution by co-depositing tin in nickel electrodeposition system. Concentration of tin was varied to investigate the hydrogen suppression effects by tin co-deposition; however it was discovered that tin ions will form oxides which are insoluble. Adding MSA and HQ will inhibit tin oxides formation, thus ensuring availability of tin ions for deposition. At tin-nickel concentration of 1:1000, it was observed that hydrogen bubbles took a longer time to form than a tin-free deposition, thus suggesting that co-depositing tin was able to suppress hydrogen evolution. However at tin-nickel concentration of 1:100, non-adherent deposits were observed which lead to inability to determine the hydrogen suppressive effects of co-depositing tin. Regardless of PEG or MSA addition, the non-adherent deposit remained unsolved. Adding sulphuric acid to the solution was proposed for future experiment and investigation as it may eliminate the issue of non-adherent deposits, therefore allowing the continuation of the investigation of the effects of co-depositing tin on hydrogen suppression.